Avaliação do desempenho e da viabilidade econômica de uma usina fotovoltaica com rastreador solar em condições de campo - Araújo, Grazielle Cristina de (2023)
Man is increasingly dependent on the use of electricity for his development. As a result, concerns about the depletion of non-renewable energy sources, in addition to the emission of polluting and greenhouse gases, have been increasing substantially. An alternative that has been widely used within renewable energy sources is photovoltaic solar energy. Brazil stands out due to its good levels of solar radiation for being in a favorable location in this regard. The objective of the present study is to evaluate and compare the performance and economic viability of two photovoltaic plants. For the performance analysis, the energy generation data for one year from two plants will be evaluated. Both plants have an installed capacity of 300kVA, with 810 modules each. The difference between them is that one has a solar tracker and the other is fixed. For the feasibility analysis, the avoided costs will be calculated, as well as the net present value (NPV), internal rate of return (IRR) and return on investment (discounted payback) rates for the capital invested in the systems. With the results obtains, it was confirmed that the plant with trackers has a higher energy generation, due to the fact the tracker follows the sun and provides a much higher incident radiation, which was already expected. The NPV of the mobile plant was R$802.647,46 and that of the fixed plant was R$1.303.752,23. For the IRR, values of 12,17% and 19,65% were obtained for the mobile plant and the fixed plant, respectively. The return in investment time was 13 years for the mobile plant and 7 years for the fixed plant. With these values, it-s possible to conclude that both systems are economically viable, and the system with trackers takes a little longer to return the value that was invested. This happens because a mobile system requires a much greater investment and, in addition, has more maintenance costs.